The Correlation between Protein, Iron, and Vitamin C Intake with Hemoglobin Levels in Pregnant Women - Sitorus, Elisabeth Prihana Rotua; Handayani, Septi; Balyas, Abi Bakring; Widayati, Ratna; Fatmaria, Fatmaria; Permatasari, Silvani (Universitas Muhammadiyah Yogyakarta, 2024)
Hemoglobin is an important component of the human body. It aims to transport oxygen and carbon dioxide. Anemia during pregnancy often occurs in the second trimester. Pregnant women tend to be vulnerable to malnutrition since their nutritional needs will increase to satisfy the needs of both the mother and the fetus. Protein intake plays a crucial role in the transportation of iron in the body. Meanwhile, vitamin C serves as a promoter of iron absorption. This research aims to determine and analyze the correlation between protein, iron, and vitamin C intake and hemoglobin levels in pregnant women at Kayon Public Health Center, Jekan Raya District. This research used an analytic observational method with a cross-sectional approach and a purposive sampling technique. Bivariate analysis was also applied by using the Spearman test. The latter results obtain a p-value of 0.748 between protein intake and hemoglobin level; a p-value of 0.222 between vitamin C intake and hemoglobin level; and a p-value of 0.050 between iron intake and hemoglobin level. There was a correlation between iron intake and hemoglobin level, yet there was no correlation between protein and vitamin C intake with hemoglobin level.